Teknik Analisis Forward Contract Hedging dengan Money Market Hedging dalam Meminimalisasi Tingkat Risiko Kerugian : Studi Kasus pada PT. Elang Perdana Tyre Industry - Sujana, Sujana; Zuhdi, Saefudin; Purwitayani, Purwitayani (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
Hedging is enterprise or entrepreneurâs step to minimize loss as result of exchange rate fluctuation. There are two implemented hedging techniques, namely Forward Contract Hedging Technique and Money Market Hedging Technique. The goal of this research is to find out how far the utilizing of the two hedging techniques will be able to minimize loss degree as result of exchange rate fluctuation compared with using non-hedging techniques (open position), thereafter comparing which of the two hedging techniques has lower cost. Analysis outcome indicates that the enterprise that does not make use of hedging techniques (open position) to ward foreign currency produces loss risk of exchange rate fluctuation for the enterprise. Keywords : Hedging; Forward Contract Hedging; Money Market Hedging